2018
DOI: 10.1016/j.jpeds.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Tuberculosis in Kenya and Risk Factors for Mortality during Treatment: A National Retrospective Cohort Study

Abstract: Objectives To describe the epidemiology of childhood tuberculosis (TB) in Kenya, assess the magnitude of TB/ human immunodeficiency virus (HIV) co-infection and identify risk factors for mortality during TB treatment. Study design We conducted a retrospective analysis of the Kenyan national TB program data for patients enrolled from 2013 through 2015. A total of 23 753 children aged less than 15 years were included in the analysis. Survival analysis was performed with censorship at 9 months and mortality was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
5
26
4
Order By: Relevance
“…Presence of low Apgar scores and low birthweight at the time of delivery were associated with higher mortality risk among infants and children in our cohort. Consistent with prior studies conducted in outpatient settings [21,22], we found higher rates of mortality among HIV-infected infants and children compared to those who were HIV-negative. Previous work has demonstrated that child factors such as young age, malnutrition, and advanced WHO HIV staging may contribute to greater mortality among children with HIV compared to children who are not infected [23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…Presence of low Apgar scores and low birthweight at the time of delivery were associated with higher mortality risk among infants and children in our cohort. Consistent with prior studies conducted in outpatient settings [21,22], we found higher rates of mortality among HIV-infected infants and children compared to those who were HIV-negative. Previous work has demonstrated that child factors such as young age, malnutrition, and advanced WHO HIV staging may contribute to greater mortality among children with HIV compared to children who are not infected [23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…In 2016 alone, the SSA region accounted for an estimated 86% of HIVlinked TB deaths (18). Kenya is one of the countries in SSA severely hit by the dual epidemic and appears among the WHO high TB and TB-HIV burden countries ranking 13 out of the 22 countries globally (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lack of individual-level data regarding the efficacy of the regimens in terms of improved pediatric TB treatment outcomes, WHO prequalification of the FDCs is the quality indicator for the purpose of this impact evaluation. Having first endorsed the FDCs in March 2017, the WHO and UNICEF released a joint statement urging “all national TB programmes to discontinue and replace the previously used medicines for children weighing <25 kg with the child-friendly dispersible TB FDCs as soon as possible” [ 4 ]. Moreover, the new child-friendly FDCs are now included on the most recent iteration of the WHO List of Essential Medicines for Children, whereas previous FDCs are not [ 1 , 5 ].…”
Section: Case Study Resultsmentioning
confidence: 99%
“…Children are, however, at increased risk of progression to active TB disease, making accurate diagnosis and prompt treatment initiation crucial in this group [4]. Moreover, TB treatment in children is considered critical to the attainment of the Sustainable Development Goal of ending preventable deaths in children by 2030.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation